Are Men more Intentional about their Careers than Women? An Exploration of the Career Trajectories of Indian Professionals - Rajesh, Saundarya; Ekambaram, Karthik; Rakesh, Anju (Prabandhan: Indian Journal of Management, 2015)
’Men are from Mars, Women are from Venus,’ goes the popular adage. Research studies the world over have only reinforced the truth behind this statement, and we now live in a society wherein the differences in attitudes, aspirations, and intentions of both the genders have been widely acknowledged. Against this backdrop, egalitarian views that have come to supersede stereotypical notions on gender roles have paved way for women careers. However, the career progress rates of men and women are drastically different; for the record, though 27% of the entry level Indian workforce is women, only 5% of senior executives in India are so, as against a global average of 20%. Where does the change in approach or attitude (towards careers) between men and women come about? At what level and what age? Is there intentionality in career pathing by men? If so, where does it stem from? This report is based on a nation-wide survey of Indian professionals (men and women) and was aimed at finding answers to these pertinent questions. The respondents employed in the corporate sector typically belonged to distinctly different career stages namely early career, mid career, and advanced or matured career stages.